Evaluation and modeling of biochemical methane potential (BMP) of landfilled solid waste: A pilot scale study - Bilgili, M. Sinan; Demir, Ahmet; Varank, Gamze (ELSEVIER SCI LTD, 2009)
The main goal of this study was to present a comparison of landfill performance with respect to solids decomposition. Biochemical methane potential (BMP) test was used to determine the initial and the remaining CH4 potentials of solid wastes during 27 months of landfilling operation in two pilot scale landfill reactors. The initial methane potential of solid wastes filled to the reactors was around 0.347 L/CH4/g dry waste, which decreased with operational time of landfill reactors to values of 0.117 and 0.154 L/CH4/g dry waste for leachate recirculated (R1) and non-recirculated (R2) reactors, respectively. Results indicated that the average rate constant increased by 32% with leachate recirculation. Also, the performance of the system was modeled using the BMP data for the samples taken from reactors at varying operational times by MATLAB program. The first-order rate constants for R1 and R2 reactors were 0.01571 and 0,01195 1/d, respectively. The correlation between the model and the experimental parameters was more than 95%, showing the good fit of the model. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Landfill; Degradation; Leachate recirculation; Methane potential; Modeling; BIOREACTOR LANDFILL; BIOGAS PRODUCTION; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels